THU0232 Pregnancy outcome in idiopathic inflammatory myopathy patients in a multicenter study. (23rd January 2014) - Vincze, M.; Váncsa, A.; Dankό, K.; Plestilova, L.; Vencovsky, J.; Gheorghe, K.; Lundberg, I.; Charles, P.; Balsam, H.; Wegier-Szewczyk, E.
Abstract : Background: Immunological changes during pregnancy are in the centre of scientific researches. We already know that immunological pathways may go wrong during pregnancy in autoimmune diseases with some general complications like fetal loss and low birth weight but we have less informations about the outcome of pregnancy in idiopathic inflammatory myopathies, polymyositis (PM) and dermatomyositis (DM). Objectives: Our aim was to assess the clinical features, organ complications, functional course, therapeutic response in patients with PM/DM according to the pregnancy status. Methods: Medical records were retrospectively revised using a standardised protocol. 23 PM/DM patients with pregnancy were identified in four countries: Hungary (n=9), Czech Republic (n=8); Sweden (n=5) and Poland (n=1). Immunological and serological characteristics were measured by ELISA, immunoblot and immuneprecipitation. Autoantibodies to Jo-1, PL-7, PL-12, EJ, OJ, SRP, PM-Scl, Ku, Mi-2, U1-, SSA, SSB were detected by LIA. We used the Fisher's exact test for statistical analysis. Results: These 23 patients had 33 pregnancies after or at the time of disease onset. 10 of them suffered from PM and 13 had DM or JDM. The most frequent symptoms were ILD, mechanic's hand, Raynaud phenomenon and arthritis. 19 pregnancies ended without complications giving life to healthy babies. In 13 cases complications, like intra-uterine growth retardation, intra-uterine death, abortion, extra-uterine gravidity occurred. These complications were most frequently seen in patients with PM than DM (p=0, 0729). The relative risk of complicated pregnancy in PM was 1, 923 (CI 95% 1, 041-3, 553). This "almost significant" finding could be caused by PM and by anti-Jo1 and anti-phospholipid autoantibodies as well, because we found these antibodies frequently associated to PM in these cases. 13 pregnancies started during the active phase of myositis and the majority of these patients didn't reach remission after the delivery. The mean weight (2599g in active disease vs. 3342g in remission) and height (48 cm vs. 51 cm) of babies was lower in the active cases and the pregnancy ended earlier than in patients with remission. Most of the affected patients used only glucocorticoid treatment during pregnancy. Conclusions: Complications during pregnancy were frequently reported in PM/DM although no myositis specific complications could be found. In patients with PM there was a tendency for a higher risk of fetal problems than in DM. Disclosure of Interest: None Declared